GAME-BASED PRACTICES AS A TOOL FOR ENHANCING MOTIVATION AND COMMUNICATIVE COMPETENCE IN INFORMAL FOREIGN LANGUAGE LEARNING (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
The rapid development of modern education and the growing importance of communicative competence in foreign language learning require the search for innovative pedagogical approaches. One of the promising directions is the integration of game-based practices into informal language learning environments. The purpose of this study is to examine the effectiveness of game-based technologies in increasing learners’ motivation and developing communicative competence in informal foreign language learning. The research was conducted among sixth-grade students at a secondary school in Semey, Kazakhstan. The study employed a pedagogical experiment including diagnostic, formative, and control stages. The results demonstrated that the systematic use of communicative games, role-play activities, and collaborative tasks significantly increased learners’ motivation, speaking activity, and confidence in using the foreign language. The findings confirm that game-based practices create favorable conditions for communicative interaction and contribute to the development of language competence in informal learning environments.